2021
DOI: 10.1177/08853282211001006
|View full text |Cite
|
Sign up to set email alerts
|

An integrated strategy for designing and fabricating triple-layer vascular graft with oriented microgrooves to promote endothelialization

Abstract: Compared with native blood vessels and existing vascular grafts, design and manufacture of vascular grafts with a three-dimensional topological structure is a key to induce cells and tissue growth, which remains an essential issue in both tissue engineering and regenerative medicine. This study sought to develop a novel triple-layer vascular graft (TLVG) with oriented microgrooves to investigate the mechanical property and endothelialization. The TLVGs were composed of electrospun Poly-ε-caprolactone (PCL)/the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Open surgical approaches might be preferred to patients with MFS mainly because of the complex and extensive involvement of the aorta (with the chance of also requiring intervention of the aortic valve), the increased risk for endoleaks and endoprosthesis migration, and the young age of the patients that may face a lifetime risk of aortic complications (15). However, endovascular and hybrid approaches have been reported in the literature (13,14,(20)(21)(22). In our case series, 88% of the procedures were performed with open approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Open surgical approaches might be preferred to patients with MFS mainly because of the complex and extensive involvement of the aorta (with the chance of also requiring intervention of the aortic valve), the increased risk for endoleaks and endoprosthesis migration, and the young age of the patients that may face a lifetime risk of aortic complications (15). However, endovascular and hybrid approaches have been reported in the literature (13,14,(20)(21)(22). In our case series, 88% of the procedures were performed with open approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Also, FET has shown that in patients with MFS and type A aortic dissection can effectively reduce the false lumen and stabilize the distal aorta (22).…”
Section: Discussionmentioning
confidence: 99%
“…53,54 The multi-layer structure of the vascular implant uses the directional microgrooves between the biomimetic layers to promote the directional growth and migration of ECs, and better mimic the arrangement of natural vascular cells. 55 Vascular implant materials containing microchannel structures both highly interconnected and circumferentially oriented can not only effectively affect the morphology, arrangement, and phenotypic changes of SMCs, but also improve the directional deposition of ECM on the surface of the material and the enrichment and polarization of macrophages, promote cell infiltration and accelerate the process of endothelialization. 56 By manipulating the micro-nano scale morphology of the material surface, the anchoring of MSCs membrane protein can be effectively regulated, and the process of differentiation into SMCs can be induced by the traction of F-actin, which is further used for the repair of vascular microenvironment.…”
Section: Surface Microstructurementioning
confidence: 99%
“…Analyzing the live-to-dead cell ratio revealed a percentage below 10% for samples containing up to 20 wt % MXene (Figure 5b). However, as the concentration of MXene in the To inhibit acute thrombosis and the migration of smooth muscle cells into the intima, a vascular prosthesis should promote rapid reendothelialization; 28 for this reason the rate of cell proliferation in the samples was studied (Figure 5c). The highest cell growth rate after 3 and 7 days was noticed on the 0 wt % MXene sample with glycerol, which mirrored the trends from the live/dead cell assay where the largest cell population was seen on the same sample.…”
Section: ■ Introductionmentioning
confidence: 99%